Incretins beyond weight and hyperglycemia management: a consensus statement by AASD - Inass Shaltout; Mona Hegazy; Amr Abdel Hady El Meligi; Shereen Abdelghaffar; Mohamed-Naguib Wifi; Alia A. Saleh; Hany Hammad; Amany Atef el Karim Abouzeid; Ebtesam Fahmy; Gehad Maghraby; Wessam ElSherief; Ghada Rabie Abdelaziz; et al. (The Egyptian Journal of Internal Medicine, 2026)
Abstract Background The global prevalence of obesity continues to rise, with 3 billion adults projected to be affected by 2030. Recent advances in anti-obesity pharmacotherapy, particularly incretin-based medications, have transformed obesity management. This consensus provides evidence-based guidelines for the clinical use of incretin-based obesity management medications (OMMs). Methods This consensus was developed through consensus narrative review and expert panel deliberation, examining current evidence for approved anti-obesity medications and emerging therapies. Literature searches were conducted in PubMed, Embase, and Cochrane databases through April 2026. Evidence quality was categorized according to study design, consistency of findings, and clinical applicability. Results Glucagon-like peptide-1 receptor agonists (GLP-1RAs) and GLP-1/gastric inhibitory polypeptide (GIP) dual agonists demonstrate substantial efficacy, with mean weight loss ranging from 5–10% with liraglutide to 21–26% with tirzepatide across various endpoints. These medications are recommended for individuals with a BMI ≥ 30 kg/m 2 or ≥ 27 kg/m 2 with weight-related comorbidities. Common adverse effects include gastrointestinal symptoms (nausea, vomiting, diarrhea), while serious complications are rare. Emerging therapies in development show promising efficacy profiles, with some triple agonists achieving > 20% weight loss in Phase 2 trials. Conclusions Incretin-based OMMs represent an important therapeutic option when combined with lifestyle interventions. Appropriate patient selection, systematic monitoring, and proactive management of adverse events are essential for optimising outcomes. Ongoing research into novel agents, long-term safety data, and cardiovascular outcomes will continue to refine clinical practice. Implementation should be guided by shared decision-making, considering individual patient factors, preferences, and healthcare system resources.